(untitled) (Journal of the College of Basic Education, 2022)
No one interested in literature affairs can deny the great poetic achievement achieved by the pioneers (Al-Sayyab and Nazek Al-Malaika) and their rich contribution in supporting the new poetic movement and their creative influence on successive generations of poets.